Landraces Traditional Variety and Natural Breed - Elkelish, Amr (IntechOpen, 2021)
Landraces - Traditional Variety and Natural Breed is a handbook of conservation and genetic diversity in plants and animals. It consists of eleven chapters covering topics such as nutritional and phytochemical content of crop landraces, vegetable landraces as valuable sources of genes for traditional farmers and future breeding processes, wild relatives/landraces of maize, and more. It is a useful resource for students studying conservation biology and individuals working in the fields of breeding and ecology.